Mapping the Variability of Soil Texture-Based on Vis-NIR Proximal Sensing - Sari Virgawati; Muhjidin Mawardi; Lilik Sutiarso; Sakae Shibusawa; Hendrik Segah; Masakazu Kodaira (Politeknik Negeri Batam, 2018)
Soil texture is one of the soil properties influencing most physical, chemical, and biological soil processes. Information on soil texture is important to support the agronomic decisions for farm management. The problem is how to provide reliable, fast and inexpensive information of soil texture in numerous soil samples and repeated measurement. The objective of this research was to generate the soil texture map based on laboratory Vis-NIR (Visible - Near Infra-Red) spectroscopy and inverse distance weighted (IDW) interpolation method. An ASD Fieldspec 3 with a spectral range from 350 nm to 2500 nm was used to measure the soil reflectance. Pipette method was used to measure the silt, clay and sand fractions. The partial least square regression (PLSR) was performed to establish the prediction model of soil texture. The predicted values were mapped and showing the information of spatial and temporal variability of soil texture. Keywords: Vis-NIR, spectroscopy, soil texture, PLSR, IDW